Applying artificial intelligence in predicting educational excellence in higher education institutions: A case study in Jordanian universities - Najdawi, Mohamed Hadi Al; Shwedeh, Fanar; Abdelmoghies, Mahmoud Mokhtar; Kitana, Abdelkarim; Ali, Ahmed (Edelweiss Applied Science and Technology, 2024)
Monitoring the responsible application of Artificial Intelligence (AI) in higher education requires the establishment of robust regulatory frameworks and thorough policy guidelines. The study concentrates on important elements that could impede the excellence of education, including issues with data security, privacy, and policies as well as legal frameworks. By examining these variables, the study aims to address the particular opportunities and difficulties encountered in this setting and to gain a deeper knowledge of how AI deployment affects educational excellence in Jordanian higher education institutions. A survey research methodology has been chosen. Institutions in Jordan that have started implementing AI or metaverse technology were given a pre-made questionnaire. The population of students in Jordanian higher education institutions, including both local and foreign students at different educational levels, is the main subject of this study. During the three-month data collection phase, the sample size was cautiously raised to more than 457 individuals in order to boost the research's robustness. The results show that the AI adoption, trust in technology (by data privacy and security), and policy & regulations in Jordanian higher institutions have significant impacts on educational excellence. Our results highlight the urgent need for policymakers to reevaluate and explain current regulatory frameworks in order to safeguard educational excellence, while also confirming the transformative possible of AI implementation in improving instructive resources and services. This study demonstrates the possible benefits of integrating AI technologies into educational backgrounds by confirming the strong correlation between AI adoption and educational excellence. In order to increase the effectiveness, usability, and caliber of educational resources and services, schools ought to think about implementing AI-driven tools and platforms.